(untitled) (Journal of Parents and Teachers, 2014)
Advertising of alcoholic beverages conveys that alcohol is going to lead us to a better life and happier. The article describes the rules of advertising of alcohol and examples of how they are not followed. In addition, activities are proposed to be performed in the classroom and involve a reflection on this topic.